Optimalisasi Sistem Pembebanan Unit-Unit Pembangkit Listrik dengan Menggunakan Metode Algoritma Genetik - Wahyuni Martiningsih; Imamul Muttakin; Wilda Annisa3 (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
In this research will optimize the loading system of power plant units 1-4 of PLTU Suralaya using genetic algorithm method. Optimization (unit of commitment) is designed using matlab software with the right purpose and constraints. Unit Commitment is a problem in the work system that determines the timing of the plant to meet the electricity needs. The method used is a system that can produce optimal loading system with a minimum cost. The simulation was conducted on 1-4 units of Suralaya power plant with total load of 33,117 MW for 24 hours. Using genetic algorithm, the cost reduction process is 5.7105%.